Translation Accuracy of Complex Sentences in Disciplinary Texts Using Google Translate (GT) - Khorina, Mulyati; Sulyaningsih, Iis; Komarawan, Yulizar (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
Google Translate has gained popularity due to some improvements to produce accurate translations since 2016. However, there is an on-going debate over the accuracy of Google Translate products. In response to this issue, the current study investigates how Google Translate interprets source language, particularly relative clauses into target language and how accurate the translation products are. This study used a qualitative case study. Moreover, the study used some chapters from an engineering textbook together with their translation version as primary data. The data in the form of relative clauses were put on a table side by side. It was then analysed and evaluated using a comparative method to find out similarity and differences. The study found that dominantly current Google Translate uses literal and expansion techniques. Furthermore, the findings suggest that GT produces accurate translation when translating relative clauses.